Keefektifan Layanan Penguasaan Konten Dengan Media Audiovisual Dalam Pemantapan Perencanaan Karier Peserta Didik Kelas X Multimedia SMK N 1 Slawi - Muhammad Arif Budiman; Usep Ilham Alfi Hasan (Cakrawala: Jurnal Pendidikan, 2017)
The research aims to 1) know the level of career planning skills learners 2) know the level of career planning skills. 3) Know the effectiveness of content mastery services trough audiovisual media at SMK Negeri 1 Slawi. The research was experimental with one group pre-test and post-test Design. Data collection used psychological scale, interview and observation. The validity of the instrument using the product moment formula. Reliability using the Spearman-Brown correlation formula. Methods of data analysis used descriptive analysis and t-test percentage. The results of the study before the given service with a content mastery audiovisual media had a percentage of 29.2% definiteness career planning (lower category). After obtaining services increased to 37.5% (medium category). Based on the results of the analysis of the t-test result of 9.344 t-count which then consulted with t-table at significance level of 5% was 1,714, so t-count > t-table. It was concluded that content mastery services trough audiovisual media was effective in students’ definiteness career planning. The research gives suggestions that counselors more varied in content mastery provision of services to assist students in making career planning appropriately.